KAJIAN NILAI BIOLOGIS DAN TOTAL BAKTERI ASAM LAKTAT DARI MP-ASI BERBAHAN BAKU JAGUNG FERMENTASI - Wardhani, Ayu Kusuma; Ivanova, Renny; Setyani, Sri; Yuliana, Neti; Astuti, Sussi (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
The objective of this research was to study the effect of tempeh yeast concentration and the lenght of corn fermentation on the biological value (BV) and NPU of complementary feeding with fermented corn. A factorial e xperiment was arranged in a Completely Randomized Design (RAL) and replicated four times. The factors studied were yeast concentration (2% and 3%) and the length of fermentation (48 and 72 h). Data were analyzed using ANOVA and further tested using LSD at 5% level of signification . The value of pH and total lactic acid bacteria were peported as means of six replications. The best treatment was found on tempeh yeast treatment at concentration of 2% , fermented for 72 hour (K1L2) with the biological value, NPU, pH and total LAB were 88,58% , 67,69%, 3.07 , and 8.84 cfu/g. Keywords: complementary infant food (MP-ASI), fermented corn flour, soybean tempeh flour